2016
DOI: 10.1016/j.bjan.2016.01.004
|View full text |Cite
|
Sign up to set email alerts
|

Efeitos das infusões de lidocaína e esmolol sobre as alterações hemodinâmicas, necessidade de analgésicos e recuperação após colecistectomia laparoscópica

Abstract: In laparoscopic cholecystectomies, lidocaine infusion had superiorities over esmolol infusions regarding the suppression of responses to tracheal extubation and postoperative need for additional analgesic agents in the long run, while esmolol was more advantageous with respect to rapid recovery from anesthesia, attenuation of early postoperative pain, and modified Aldrete recovery (MAR) scores and time to reach MAR score of 9 points.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 15 publications
2
3
0
Order By: Relevance
“…Our study also shows that the postoperative pain free period was significantly more in the Group B. A systemic review on intravenous lignocaine infusion preoperatively concluded that there was a decreased anaesthetic drug requirement intraoperatively, decreased requirement of postoperative analgesics, and also had lower pain scores ( 12 ).…”
Section: Discussionsupporting
confidence: 59%
“…Our study also shows that the postoperative pain free period was significantly more in the Group B. A systemic review on intravenous lignocaine infusion preoperatively concluded that there was a decreased anaesthetic drug requirement intraoperatively, decreased requirement of postoperative analgesics, and also had lower pain scores ( 12 ).…”
Section: Discussionsupporting
confidence: 59%
“…Clinical studies investigating the effect of intraoperative IV lidocaine in comparison to esmolol on postoperative opioid and pain scores have shown conflicting results. Similar to our findings, Dogan et al found no difference between the two groups in postoperative 24 h opioid consumption after laparoscopic cholecystectomy [16]. In contrast, Kavak Akelma et al found significantly less fentanyl requirement in patients receiving esmolol than those receiving lidocaine infusion or placebo in the first 24 h of surgery [17].…”
Section: Discussionsupporting
confidence: 89%
“…Early recovery is one of the relevant clinical outcomes after minimally invasive surgery. It is reported that patients in esmolol group achieve early discharge criteria from the PACU as compared to lidocaine group [16]. In the same study, patients receiving lidocaine had RSS scores higher than esmolol at 10 min post-extubation.…”
Section: Discussionmentioning
confidence: 78%
See 2 more Smart Citations